Profitability study for a paper recycling facility in Iceland - Sigríður Ólöf Valdimarsdóttir 1993- (2021)
This thesis was done in collaboration with Pure North Recycling, an Icelandic plastic recycling company. Currently all Icelandic paper waste is shipped abroad for recycling. The purpose of this study was to explore if it is financially feasible for Pure North to add paper recycling to their business where the paper is recycled into molded fibers. To answer this question a financial assessment was conducted followed by sensitivity analysis to assess the risk. Four operation cases were analyzed to study two recycling machines, and to compare the use of methane gas and geothermal heat as source of energy for the recycling process. The study showed that Icelandic paper recycling can be profitable if the demand for molded fiber products is high enough. However, a more detailed market research is needed to answer which machine is better suited, or even if the market is large enough for the project to be profitable. The results showed that geothermal heat is always a financially better option as an energy source for the recycling. Since the results were given dependent on possible demand, Pure North will have to use the sensitivity results to help them make the investment decision when they have a clearer picture of the market. The sensitivity results showed that sales price and sales quantity are the most sensitive variables, making it even more important to perform a detailed marked research before any investment decision is made. Þetta verkefni var unnið í samstarfi við íslenska plast endurvinnslufyrirtækið Pure North Recycling. Tilgángur rannsóknarinnar var að kanna hvort hagstætt væri fyrir Pure North að endurvinna pappír á Íslandi í pappamót, en í dag er allur pappa úrgangur sendur úr landi til endurvinnslu. Arðsemismat var framkvæmt ásamt næmnigreiningu til að meta fjárhagslega áhættu verkefnisins. Fjögur tilfelli voru skoðuð til þess að bera saman tvær misstórar endurvinnsluvélar, ásamt því að finna hvort metan gas eða jarðvarmi væri hagstæðari orkugjafi. Rannsókin sýndi fram á að pappa endurvinnsla getur ...